An examination of supply chain management using emerging technologies - Abdallah, Tayebi; Djelloul, Benba; Seddiki, Ahmed (The International tax journal, 2025)
Because so many people could not get hand sanitizer, cleaning products or paper goods during the pandemic due to supply chain problems, many consumers reached out to the media for answers. Around 95 percent of the Fortune 1000 companies said that China has led to problems for their supply chains. Supply chain issues can be solved with new inventions. These improvements make the system more reliable, pollution and trash go down, moving goods are made simpler and prices are greatly decreased. It explores methods for managing supply chains using Industry 4.0, examines automation to improve supply chain processes and reviews supply chain management as it stands now and its main issues. Based on (Woods, 2024), Nasereddin (2024) and (Tong, 2024), along with other sources, the observations in this book are found in the most recent numerical information.